Pengaruh Kualitas Pelayanan dan Harga Terhadap Kepuasan Pelanggan pada UMKM Burgerax Karawang - Arziel Pramudya; Sungkono (PENG: Jurnal Ekonomi dan Manajemen, 2024)
This research aims to investigate the sales quality in terms of customer sales volume of Burgeralx MSMEs in Kalralwalang. By carrying out a qualitative approach, the product data was collected through a direct survey of Burgeralx customers in the Balgali locality in Kalralwalng, with a focus on aspects such as digital marketing, sales speed, product quality, and product perception. Alkaln digital analysis is carried out using statistical techniques to determine the extent to which internal service quality contributes to customer satisfaction. The result of this research is that it can provide valuable benefits for Burgeralx MSMEs in improving the distribution strategy in implementing legal marketing in order to increase the level of customer satisfaction in preventing mutual communication at local stores in Kalralwalng.